La question de l’immigration au Royaume-Uni dans les années 1970 : le Parti conservateur, l’extrême droite et l’« effet Powell » - Stéphane Porion (Revue Française de Civilisation Britannique)
This paper aims to analyse the evolution of the Conservative Party’s stance on immigration in the 1970s, by focusing both on the radicalization of their political discourse and the expansion of the National Front until Margaret Thatcher’s 1979 victory, which in turn marked its significant decline. First, the analysis will focus on the 1971 Immigration Law, showing not only how the Conservatives continued to pursue a restrictive policy stemming from the previous decade, but also what the consequences of Britain’s membership in the EEC on the 1971 legislation were. The Heath years can be better accounted for if one takes into account Enoch Powell’s influential ideas on the immigration debate, publicly put forward in his April 1968 « Rivers of Blood » speech, and the Conservative government’s strain to handle the 1972 Uganda crisis. Furthermore, Thatcher, who became leader of the Conservative Party in 1975, pushed her party towards a harsher stance on immigration which was to result in a new restrictive law in 1981, well prepared beforehand in the Opposition years in the late 1970s. That period of time undoubtedly embodied the beginning of the National Front’s strong decline after a decade of expansion since its creation.